An exploration of the care needs of frail older persons in Namibia: perspectives and experiences of formal and informal caregivers - Zamuee, Charmill (Department of Social Development, 2022)
The adequate care of older persons is a major global concern and countries are examining ways to respond to these needs, especially the needs of frail older persons in the care environment. Important strides have been made in developed countries but progress has been slow in less developed countries in the Global South and limited information exists on the care needs of frail older persons and lived experiences of formal and informal caregivers. This thesis examines the care needs of frail older persons in Namibia. Namibia has only recently been liberated from colonial rule by Germany and apartheid South Africa. During this time black communities were disenfranchised, resource-scarce and living under poor conditions. For older persons, this meant unequal treatment, social exclusion and denial of access to decent care. The aim of this study was to provide an in-depth understanding of the needs of frail older persons in the care environment in Namibia by examining the lived experiences of caregivers and analysing policy. Using a qualitative methodology, the study collected primary data from formal and informal caregivers based on semi-structured interviews and focus groups. The data analysis relied mainly on coding strategies under Atlas-ti and qualitative content analysis. The secondary data were collected from legislation, government policy documents, journals and other public reports. The finding revealed that Namibia's history has entrenched the current situation of unmet needs of frail older persons, exacerbated by inadequate policy protection. These limitations were highlighted by the Covid-19 pandemic. The study also found that the effective care of frail older persons is only possible through stakeholder engagement and cross-sectoral collaboration. The study therefore recommends that government should undertake a process of social reforms to ensure that the needs of this group are prioritised, that a performance framework should be implemented to ensure delivery and that all stakeholders should be mobilised. The study has contributed to these outcomes by suggesting a model for needs assessment of frail older persons, especially during the Covid-19 pandemic. This model could be used to improve care practices, serve government in evidence-based policy making and provide a useful analytical tool for scholarship.